Performance of cover crops under two irrigation regimes in the Coastal Tablelands region of Brazil - Nicole,Lucas Rodrigues (2021)
ABSTRACT There is currently a lack of information regarding the performance of cover crops grown in the Coastal Tablelands region in the North of the Brazilian state of Espírito Santo, where zero tillage is increasingly being adopted. The objective of this study was to evaluate the agronomic performance of six cover crops (ruzi grass, jack bean, and the millets ADR 300, ADR 500, ADRf 6010, and BRS 1501) under two irrigation regimes. A field experiment setup was based on randomized blocks with split plots and four repetitions. Shoot dry matter content, plant height, leaf area, chlorophyll fluorescence, and root growth of the cover crops were evaluated. The irrigation regime influences the agronomic performance of most of the cover crops, with the exception of jack bean and ADRf 6010 millet, which were tolerant to water deficiency, based on our evaluations of the variables shoot dry matter, plant height, and leaf area. In terms of biomass production, ADRf 6010 millet is the most suitable crop for use in conservation systems under conditions of water stress in this region.